Sub-lethal doses of Nucleopolyhedrosis Virus and synthetic ınsecticides alter the biological parameters of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae). - Allah Dita Abid; Syed Muhammad Zaka; Shafqat Saeed; Naeem Iqbal; Muhammad Nadir Naqqash; Muhammad Sohail Shahzad (PLoS ONE, 2021)
Resistance management is very important for devising control strategies of polyphagous insect-pests like Helicoverpa armigera Hübner (Lepidoptera: Noctuidae). Considering the importance of resistance management, demographic features of selected and unselected populations of H. armigera were studied in 6 different treatments viz. emamectin benzoate, Helicoverpa armigera Nucleopolyhedrosis Virus (HaNPV), emamectin benzoate+HaNPV, spinetoram, spinetoram+HaNPV and control. Higher values for fecundity, intrinsic rate, the finite rate of increase (λ) were recorded in the control of selected as compared to the rest of treatment. Similarly, higher values for these population parameters viz. oviposition days, fecundity, intrinsic rate, the finite rate of increase were calculated in the unselected control. Similarly, net reproductive rate (R0) for selected and unselected control was higher as compared to the rest of the treatments. It may happen because these kinds of selection pressures can result in decreased fitness of the test insect thus decreased fitness of H. armigera in different treatments was observed as compared to the control. Additionally, quicker development of susceptible insects was observed because susceptible insects were growing without any stressor (xenobiotics) as compared to the rest which contributed to their faster development.